Study the effects of an addition of titanium dioxide (TiO2) on the mechanical and thermal properties of polypropylene-rice husk green composites - Awang, Mohamad; Wan Mohd, Wan Roslina; Sarifuddin, Norshahida (Institute of Physics Publishing, 2019)
New composites based on polypropylene as polymer matrix reinforced rice husk have been developed. The improvement of mechanical and thermal properties can be achieved by the addition of inorganic filler namely titanium dioxide (TiO ). In this work, two series of composites formulation of polypropylene reinforced rice husk with and without TiO incorporation were prepared. The composite was firstly melt compounding with a twin screw extruder and then were injection molded. Mechanical tests were applied to obtain tensile strength, Young's modulus and elongation at break. Morphology of fractured surface of the composites also was observed using Scanning Electron Microscope as well as thermal properties was analyzed by Thermogravimetric Analysis (TGA). The results showed that the composites with an inclusion of inorganic filler TiO gave better mechanical properties than the composites without inclusion of TiO and pure PP. The maximum value of tensile strength which was 41.2 MPa represented by the composites formulation of PP/RH-10 wt%/TiO . Generally, Young's modulus This site uses cookies. By continuing to use this site you agree to our use of cookies. To find out more, see our Privacy and Cookies policy.  2 1 1 2 wroslinamohd@gmail.com School of Ocean Engineering, Universiti Malaysia Terengganu, 21030 Kuala Nerus, Terengganu, Malaysia Department of Manufacturing and Materials Engineering, Kulliyyah of Engineering, IIUM, Jalan Gombak, 53100 Kuala Lumpur, Selangor, Malaysia Wan Roslina Wan Mohd https://orcid.org/0000-0001-8162-0946 Received 31 January 2018 Accepted 20 March 2019 Accepted Manuscript online 20 March 2019 Published 5 April 2019 Method: Double-blind Revisions: 3 Screened for originality? Yes Mohamad Awang et al 2019 Mater. Res. Express 6 075311 https://doi.org/10.1088/2053-1591/ab1173 Buy this article in print 1 2 2 2 2 2 2 of PP/RH-40 wt%/TiO composites showed increment which was 1086.16 MPa and 635.48 MPa higher than that of pure PP and PP/RH. Elongation at break decreased in PP/RH/TiO as compared to PP/RH composites. Scanning electron microscope (SEM) micrographs show improved interaction between RH and PP matrix by having a good interfacial adhesion as a result of TiO inclusion in PP/RH composites. Thermogravimetric analysis (TGA) indicated that thermal stability of PP/RH/TiO composite was increased as compared to pure PP and PP/RH composites. Incorporation of inorganic filler TiO into PP/RH significantly enhanced mechanical properties and thermal stabilities of the green hybrid PP/RH/TiO composites.